2020
DOI: 10.1124/jpet.120.265595
|View full text |Cite
|
Sign up to set email alerts
|

ELX-02 Generates Protein via Premature Stop Codon Read-Through without Inducing Native Stop Codon Read-Through Proteins

Abstract: ELX-02 is a clinical stage, small-molecule eukaryotic ribosomal selective glycoside acting to induce read-through of premature stop codons (PSCs) that results in translation of full-length protein. However, improved read-through at PSCs has raised the question of whether native stop codon (NSC) fidelity would be impacted. Here, we compare read-through by ELX-02 in PSC and NSC contexts. DMS-114 cells containing a PSC in the TP53 gene were treated with ELX-02 and tested for increased nuclear p53 protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…ELX-02 is a eukaryotic ribosomal selective glycoside which displays preferential binding to the eukaryotic ribosome and promotes premature stop codon read-through [3] . Evidence of native stop codon read-through has not been detected [4] , consistent with conserved cis-element factors that improve native stop codon fidelity. ELX-02 has been evaluated in Phase 1 clinical trials, where it was found to be well tolerated with pharmacokinetic properties consistent with preclinical evaluations [5] .…”
Section: Introductionmentioning
confidence: 86%
“…ELX-02 is a eukaryotic ribosomal selective glycoside which displays preferential binding to the eukaryotic ribosome and promotes premature stop codon read-through [3] . Evidence of native stop codon read-through has not been detected [4] , consistent with conserved cis-element factors that improve native stop codon fidelity. ELX-02 has been evaluated in Phase 1 clinical trials, where it was found to be well tolerated with pharmacokinetic properties consistent with preclinical evaluations [5] .…”
Section: Introductionmentioning
confidence: 86%
“…This selectivity profile Figure 3 was hypothesized to improve nonsense mutation read-through while mitigating drug-induced tolerability attributed to binding to the mitochondrial ribosome. Optimization led to ELX-02 and other similar molecules showing greater read-through activity in a plasmid-based dual-luciferase assay and restoration of full length, functional protein by ELX-02 in cellular assays while simultaneously demonstrating improved cellular tolerability [20,23,24]. Normally, ribosomes translate mRNA to produce full-length protein and that mRNA transcript is then still available for additional rounds of translation.…”
Section: Chemistrymentioning
confidence: 99%
“…In an exemplar nonsense mutation model system, ELX-02 produced significant read-through of the premature stop codon found in TP53 mRNA in DMS-114 cells, resulting in increased p53 protein expression and an increased mRNA content that is consistent with decreased NMD [24]. Native stop codon read-through protein products were not observed in either DMS-114 cells or in clinical samples from subjects dosed with ELX-02 in studies EL-001 or EL-006 (as described in Section 3 below).…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…ELX-02 can restore the expression of nonsense mutated CFTR in CF models by interfering with the NMD process and/or stabilizing the mRNA. ELX-02 exerts its nonsense suppressor activity with improved efficacy and a 100-fold lower antibiotic activity compared with first generation aminoglycosides [186,212]. ELX-02 showed a ten-fold improved PTC-readthrough efficacy compared with gentamicin in restoring nonsense mutated CFTR gene in vitro and in vivo [213].…”
Section: Aminoglycoside Derivativesmentioning
confidence: 99%